Compliance of Financial Statements of Small and Very Small Companies with the Provisions of Business Accounting Standards - Balkytė, Giedrė; Kvekšienė, Milda; Striaukaitė, Lina (Socialiniai tyrimai, 2020)
At the end of the financial year, companies’ accounting departments prepare sets of financial statements which are the most important regulated information source for assessing the company’s financial state and its performance. Article 16 of the Law on Financial Statements of Enterprises of the Republic of Lithuania states that financial statements are prepared in accordance with this Law, Business Accounting Standards (BAS) or International Accounting Standards. In the Explanatory Note it must be indicated according to which accounting standards the financial statements were prepared. According to the Lithuanian Department of Statistics, the domestic market is dominated by very small and small enterprises. These companies have a significant impact on the country’s economy. The financial statements of most of them are not audited and this lack of audit can cause some country-wide problems. The audit of annual reports according to Article 24 of the Law on Financial Statements of Enterprises of the Republic of Lithuania must be performed in enterprises if at least two indicators on the last day of the financial year exceed the following values: 1) the value of assets is 1,800 thousand euros; 2) net sales revenue during the budgetary year are 3,500 thousand euros; 3) the average annual number of employees according to the list during the budgetary year is 50 employees. The issue of accounting and financial statements’ quality were examined in various aspects not only by Lithuanian authors Legenzova (2016), Legenzova and Kancereviciute (2012), Guptor and Rudzioniene (2018), Lakis and Miniotaite (2016), Miniotaite (2017), Deveikis (2018, 2020), but also foreign authors such as Abbod et al. (2018), Franczak (2019), and Goncharenko et al. (2016). Most of these authors indicate compliance with the provisions of the regulations to be among the important factors determining the quality of financial statements. In order to improve the quality of financial statements in Lithuania, new initiatives are regularly brought forward to the Ministry of Finance and the Parliament to introduce measures in legislation that would improve the quality of financial statements of for-profit limited liability units. In 2015, the Parliament’s Audit Committee drafted a package of legislative changes. It proposed measures to improve the quality of financial statements as well as obliged entities to provide mentioned statements to the Register of Legal Entities for proper monitoring of the submitted documents. Those changes in the legislation, however, were not implemented. To implement public policy in the field of financial liability, the Authority of Audit, Accounting, Property Valuation and Insolvency Management (AVNT) for several years has been conducting a quality survey of the financial statements (Explanatory Notes) of 100 companies. In performing the analysis of the financial statements of the companies, AVNT assessed whether they comply with the provisions of the Business Accounting Standards and the submission of compulsory information in accordance with the requirements of the 6th Business Accounting Standard of “Explanatory Note”. For this study, unaudited companies are selected on the basis of the highest net sales revenue and the highest value of assets on the balance sheet. The results of this study show that the quality of financial statements is not improving (AVNT, 2020). It is difficult for small and very small companies to constantly monitor and comply with the requirements and alterations of the financial statements preparation standards. This gives rise to the following question: How much do the financial statements of small and very small companies match with the provisions of the Business Accounting Standards? Linartas (2020) argues that the quality of financial statements is poor in companies that are managed by one or more owners. This might be due to the fact that the owners of such companies receive the information about their companies’ financial state and performance directly and have no interest in disclosing it in the financial statements. The object of the research are sets of financial statements of small and very small enterprises. The aim of the research is to analyse the compliance of the financial statements of small and very small enterprises with the provisions of the Business Accounting Standards. The objectives of the research are the following: 1. To assess the compliance of the general composition of financial statements of small and very small enterprises submitted to the General Meeting of Shareholders and the Register of Legal Entities with the provisions of 1st BAS “Financial Statements” and the Law on Financial Statements of Enterprises; 2. To analyse the compliance of the individual parts of financial statements of small and very small companies with the provisions of the Business Accounting Standards. The chosen methodology for this research includes systematization, grouping and summarization of data as well as document content analysis. The research methods are the analysis and synthesis of legal acts regulating the composition of financial statements and requirements for the preparation of separate reports, as well as of scientific literature. Furthermore, systematization, grouping and summarization of data and analysis of document content were applied to the analysis of financial statement data. In order to analyze the compliance of the financial statements of small and very small enterprises with the provisions of the Business Accounting Standards, 72 sets of financial statements of private limited companies operating in Western Lithuania were obtained. The criteria for small and very small enterprises were met by unaudited reports of 66 companies. The research shows that in some companies the General Meeting of Shareholders approves financial statement set forms that do not comply with the Law of Financial Reporting and the provisions of Business Accounting Standards. However, other forms of digitized sets of reports that are in compliance with the requirements of the Register of Legal Entities are afterwards being submitted to this institution. Furthermore, after examining the compliance of the items of the separate financial statements of small and very small enterprises with the provisions of the Business Accounting Standards, some irregularities have been identified. Sums were not included in the entry of deferred charges in the balance sheet as accorded in the 2nd BAS “Balance Sheet”. Some companies do not calculate the cost of sales or do not distinguish the amount of losses in the profit-and-loss account as accorded in the 3rd BAS “Income Statement”. Some companies do not indicate the number of employees in the general part of the explanatory note as accorded 6th BAS “Explanatory Note” and there is no part of accounting policies and notes. Sometimes the notes are not numbered and therefore in other reports there is no reference to the remarks section of the Explanatory Note. There is in certain cases no comparative information. Finally, in some cases the parts of the accounting policies and notes are combined into one section.